Pengalaman Pengguna (User Experience) Pada Aplikasi Electronic Tax (E-Tax) di Kota Palembang - Aryansah, Januar Eko; Rahmawati, Athifah (Spirit Publik: Jurnal Administrasi Publik, 2023)
Palembang is one of the autonomous regions of Indonesia that already applying the concept of E-Government through the Electronic Tax program (E-Tax) can increase local government income through electronic tax collection. As the online tax system on the E-Tax application grows, on the other side of the user experience is one of the key factors in supporting the success of building an application. Therefore, a review should be given as to whether the application has been appropriate to the user's needs in the self-sufficient and honest tax payment of  Palembang. This type of research uses qualitative methods with a string of string phenomena. Researchers conducted deep interviews for eleven people to measure the user experience so that users' opinions on the E-Tax application could be known. The study found that the quality of the E-Tax application in Palembang remains inadequate to meet users' need for independent tax payments. However, E-Tax in use in the Palembang makes it easier for users in the form of a tax accounting to report to the municipal revenue agency. Of their function and usage, the 3 features most often accessed by users on the e-tax application have not completely met the criteria of usability theory in user experience except on memorability variable.